SUN-504 A Case of T3 Thyrotoxicosis - Peloquin, Isabelle Daneault (J Endocr Soc, 2020)
Clinical vignette ENDOCRINE SOCIETY 2020 Title: A case of T3 thyrotoxicosis induced by a dietary supplement. A 24 yo man consulted for a 2 weeks history of diaphoresis, fatigue, insomnia, palpitations and headache associated with a 20 pounds lost. The patient didn’t have a goiter or any signs of orbitopathy. The results revealed a free T3 level of 45.8 pmol/L upon arrival (normal (N) 3.4- 6.8 pmol/L), free T4 level of 6.4 pmol/L (N 11.0–22.0 pmol/L) and TSH level less than 0.005 mUI/L (N: 0.35 to 3.50 mUI/L). Facing those results, a complete review of the patient medication and natural product consumption was done. The patient revealed that he was using, since a month, a vegetable extracts nutritional supplement that didn’t included iodine. He was asked to stop the nutritional supplement and propranolol 10 mg twice daily was prescribed. Thyroid function tests were done 3 days after. The results demonstrate a fT3 level of 4.6 pmol/L, a fT4 level of 5.6 pmol/L and a TSH that still suppressed. A thyroid scintigraphy was performed 7 days later and showed a homogeneous uptake of 18.5% (N 7.0% – 35.0%). We saw the patient 2 weeks later and we ordered another thyroid function test with TSH receptor antibodies, TPO antibodies and thyroglobulin. The results were the following: fT3 of 5.1 pmol/L, fT4 of 12.1 pmol/L, TSH of 2.31 mUI/L, thyroglobulin of 19.8 ug/L (N: 1.4 – 78) and normal levels of antibodies against TPO and TSH receptors. To confirm the contamination of the nutritional supplement by fT3 we used a plasma pool of normal patients in which we measured thyroid function tests at baseline and after we have added the nutritional supplement powder to reflect the dose suggested by the manufacturer. The results showed that fT3 level increased by 36.5%, fT4 by 11.2% and TSH didn’t changed. The powder was then analyzed by an external laboratory that wasn’t able to demonstrate the presence of fT3 nor fT4. The two diagnostic possibility facing those results were that the powder induced an interference with immunoassay used to measure fT3 and fT4 but not TSH or thyrotoxicosis induced by the nutritional supplement with limitation in the technique that tried to identify fT3 in the powder. Given the presentation of the patient, we are convinced that this case represents a thyrotoxicosis induced by a nutritional supplement. In conclusion, Graves’ disease is responsible for 60–80% of the cases of hyperthyroidism. However, there are few cases reports of thyrotoxicosis induced by nutritional supplement(1,2,) but some studies demonstrate the presence of thyroid hormone in significant amounts in some commercially available health supplements(3). This case highlights the importance of verifying exposition to medications and natural products when confronted to cases of thyrotoxicosis. 1.Regina A et al. MMWR Morb Mortal Wkly Rep. 2016 2. Panikkath R et al. Am J Ther. 2014 3. Kang GY et al. Thyroid. 2013